Italian cultural adaptation of the Memorial Anxiety for Prostate Cancer scale for the population of men on active surveillance. Issue 3 (June 2018) - Alvisi, Maria F.; Repetto, Claudia; Rancati, Tiziana; Badenchini, Fabio; Magnani, Tiziana; Marenghi, Cristina; Villa, Silvia; Nicolai, Nicola; Salvioni, Roberto; Avuzzi, Barbara; Valdagni, Riccardo; Bellardita, Lara; et al.
Purpose: The Memorial Anxiety Scale for Prostate Cancer (MAX-PC) is a self-report questionnaire that was developed in English to assess prostate cancer (PCa)-related anxiety. The aim of this study was to perform a cultural adaptation for the tool to be used in a population of Italian men on active surveillance (AS). Methods: A total of 222 patients with localized PCa who were recruited for the Prostate Cancer Research International: Active Surveillance (PRIAS) protocol completed the MAX-PC. Psychometric analysis was performed to assess reliability indexes. A Spearman rank correlation was used to test the association between MAX-PC scales and other questionnaires and was used for longitudinal analysis. Results: Cronbach coefficients and item to total correlation demonstrated good internal consistency. Some items related to the repetition of the PSA test showed a large floor effect and thus were poorly effective in measuring anxiety for PSA testing in patients on AS. Confirmatory factor analysis partly failed to reproduce the structure of the original version. A modified version of MAX-PC, excluding the items with a large floor effect, was thus considered for AS patients. Factor analysis on this version demonstrated considerable consistency with the presence of 3 subscales: anxiety related to PCa, anxiety related to PSA testing, and anxiety related to the fear of tumor progression. Longitudinal analysis showed an acceptable validity over time. The MAX-PC was correlated with the anxious preoccupation subscale of the Mini-Mental Adjustment to Cancer scale. Conclusions: A slightly modified version of the MAX-PC was developed for use in Italian men on AS. This instrument appears to be a valid and reliable tool that measures anxiety in men with PCa who are enrolled in AS programs.